Stress Related Temporomandibular Joint Disorders - A Comparative Study between Preclinical and Clinical Undergraduate Students of Dentistry - Munazza Sharfuddin1 , Ayshwarya Muralidharan2 , Premalatha Shetty3 , Aditya Nandan4 , Animesh Jain5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This cross-sectional study compared the proportion and severity of stress related TMD, genderpredilection and influence of parafunctional habits in preclinical and clinical undergraduate students ofdentistry.Method: The data was collected using Fonseca’s Anamnestic index and Zung’s Self-rating Anxiety Scale.The results were analyzed as proportions and percentage. Chi square test was used. A ‘p value’ of less than0.05 was considered as significant.Results: Mild to moderate anxiety levels were seen in 6.4% females and 3.4% males .According to the FAI,48.2% females and 67.8% males did not have TMD. Mild, moderate and severe TMD were seen in 41.1%,9.2% and 1.4% of the females and 27.1%, 5.1% and 0% males respectively.Conclusion: While the proportion of stress was higher in preclinical students, TMD was higher in clinicalstudents. TMD observed in clinical students could be a manifestation of the stress they experienced in theirformer years